Maximizing fodder yield of teosinte (Euchlaena mexicana) through sowing dates and mixed fodder cropping management - Khanal, B.; Devkota, N. R.; Tiwari, M. R.; Gorkhali, N. A. (Journal of Agriculture and Forestry University, 2020)
Teosinte (Euchlaena mexicana) is one of the most popular summer growing cereal fodder, rich in energy, dry matter (DM) and other nutrients, yet productivity of this fodder in Nepal has not been achieved as expected due to several important factors including cultivation management and sowing dates. An experiment was done during April to August 2018 at Directorate of Agricultural Research, NARC, Province-5, Khajura, Banke by using Split Plot design with the objective to identify the appropriate sowing dates in relation to possible combination of local fodder legumes with teosinte. It was expected that best possible combination of fodder legumes with teosinte would increase both herbage mass as well as quality aspects through increased productivity. Accordingly main plot treatments were sowing dates (April 18, May 3, and May 18) and sub-plot treatments were set as combination of fodder cowpea, lablab bean, and rice bean, each with teosinte, and sowing of teosinte as sole crop. Findings revealed that plant height, leaf length, tiller density of teosinte, and number of branches and trifoliate leaves of fodder legumes had contributed significantly to the cumulative herbage mass. Significantly highest green herbage and dry herbage mass (p<0.001) was obtained if these fodder species were sown in April 18 as compared to other dates of sowing. The combination of teosinte and cowpea had yielded significantly higher herbage mass (p<0.001) compared to others fodder species combinations. Preliminary findings of this research thus indicate the possibility of promoting mixed cultivation of teosinte with fodder cowpea in order to increase both herbage mass and quality.